Business Valuation in Terms of Indicators of Sustainable Development - Leontina Pavaloaia (CES Working Papers, 2013)
The indexes regarding the sustainable development have an important role in the decision-making process and that is why several bodies and institutions are concerned about their development. This fact happens not only at macro-level, but also at micro-level, the entities being encouraged to take into account the sustainable development principles and to relate its individual performances to the environment in which they operate (local, regional, global). The usage of the indexes regarding the sustainable development offers information regarding the evolution in time helps at identifying the possibilities of improving the activity and the weaknesses; they can be used in order to establish and achieve the objectives, the values being easily communicated both within and outside the company. A main disadvantage is the aggregation level, which hinders comparisons. This paper analyzes the information regarding the sustainable development published by the companies ranked at the Stock Exchange of Bucharest in the 1st category and the subsidiaries of 30 national companies.
Keywords: Q01; Q56; 330; sustainable development; environmental indicator; microeconomic Romania